EFFECT OF NITROGIN, HUMUS AND GIBBERELLIC ACID 0N VEGETATIVE GROWTH OF ALMOND SEEDLINGS AND ITS BUDDING SUCCESS PERCENTAGE - Jassim AL-A,areji; Ahmed T. Al Hayyat (Mesopotamia Journal of Agriculture)
Almond seedlings which were grown at fruit field / Horticulture and Land Scape Design / College of Agriculture and Forestry during 2012 growing season were fertilized with three levels of nitrogen (0, 50 and 100 gm N/seedling ) by using urea fertilizer (46 % N) as a sourse of nitrogen, three levels of humus liquid fertilizer (18% humic acid) (0, 5 and 10 ml humus/L/seedling) and foliar spray with two concentrations of gibberellic acid (0 and 75 mg GA3 / L), to improve seedlings vegetative growth and budding success percentage. Results indicated that the treatments of 100g N/seedling +5 ml humus / L / seedling + 0 mg GA3 / L. gave the highest means leaves N concentrations (1.14 %) and seedling leaves area (2119.40 cm2/seedling), Meanwhil the treatment of 100g N/seedling +10 ml humus / L / seedling + 0 mg GA3 / L. gave the highest means of leaves chlorophyll (60.20 SPAD unit) and budding successes (100 %). The highest means of seedling height increament was obtaind at the treatment of 100g N/seedling +0 ml humus / L / seedling + 0 mg GA3 / L. (100.49 cm).